Eksistensi Play dan Labour dalam Penggunaan In-App Game pada Aplikasi Lokapasar Shopee - Abyzan Syahadin Bagja Dahana (Universitas Tidar, 2024)
This study aims to describe the practice of play and labour in the use of in-app games on marketplace applications. Various researchers have viewed in-app games or games within marketplace mobile applications such as Shopee as gamification efforts that have the potential to improve the consumer experience and thus encourage transactions. Nevertheless, gamification within marketplace applications has the potential to blur the boundaries between